Elevated C-Reactive Protein and Erythrocyte Sedimentation Rate Correlates with Depression in Psoriasis: A Chinese Cross-Sectional Study - Tan M; Luo Y; Hu J; Hu K; Li X; Yang J; Chen J; Zhu W; Kuang Y (Dove Medical Press, 2023)
Minjia Tan,1- 3,* Yan Luo,4,* Jingjin Hu,1- 3 Kun Hu,1- 3 Xingyu Li,1- 3 Jing Yang,1- 3 Junchen Chen,1- 3 Wu Zhu,1- 3 Yehong Kuang1- 3 1The Department of Dermatology, Xiangya Hospital, Central South University, Changsha, People's Republic of China; 2National Clinical Research Center for Geriatric Disorders (Xiangya Hospital), Changsha, People's Republic of China; 3Hunan Engineering Research Center of Skin Health and Disease; Hunan Key Laboratory of Skin Cancer and Psoriasis (Xiangya Hospital), Changsha, People's Republic of China; 4Department of Dermatology, Jiangxi Provincial People's Hospital, Nanchang, People's Republic of China*These authors contributed equally to this workCorrespondence: Yehong Kuang; Wu Zhu, Email yh_927@126.com; zhuwu70@hotmail.comPurpose: Psoriasis patients often suffers from anxiety and depression. Inflammation, anxiety, and depression have been associated with each other, but the relationship has not been examined in subjects with psoriasis. The primary objective was to investigate the relationship between the C-reactive protein (CRP) and the erythrocyte sedimentation rate (ESR) and depression among patients with psoriasis.Methods: In this case-control, cross-sectional study, 239 individuals with psoriasis and 142 with healthy controls (HCs) were recruited. Psychological as well as clinical, and laboratory data were collected.Results: 50.2% of subjects with psoriasis reported depressive symptoms, compared with 26.8% of HCs. 39.7% and 17.6% observed anxiety symptoms in psoriasis patients and HCs. The odds of anxiety (AOR= 3.123; 95% CI = 1.851- 5.269) and depression (AOR= 2.698; 95% CI = 1.690- 4.306) were higher in psoriasis patients relative to HCs. Furthermore, the elevated CRP (AOR =2.139; 95% CI = 1.249- 3.663) and ESR (AOR =1.827; 95% CI = 1.078- 3.096) were the risk factors of depression in patients with psoriasis. The threshold for distinguish psoriasis patients in depression was 3.24 (area under the curve [AUC], 0.605; sensitivity, 0.57; specificity, 0.64) for CRP and 26.5 (AUC, 0.632; sensitivity, 0.52; specificity, 0.73) for ESR.Conclusion: A substantial prevalence of anxiety and depression symptoms was observed in Chinese psoriasis subjects, and the odds were much higher in psoriasis patients relative to HCs. The elevated CRP and ESR level was significantly associated with depression in psoriasis patients. Besides, the discrimination capability of CPR and ESR on depression further indicates the extra value of inflammatory biomarkers in the management of psoriasis patients.Keywords: psoriasis, depression, anxiety, C-reactive protein, erythrocyte sedimentation rate